TAWARRUQ BERASASKAN KREDIT PRABAYAR TELEFON: TINJAUAN TERHADAP PRODUK PEMBIAYAAN PERIBADI DI RHB ISLAMIC BANK(TAWARRUQ CREDIT BASED PREPAID PHONE: REVIEW OF PRODUCTS IN THE RHB ISLAMIC BANK PERSONAL FINANCING) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
Tawarruq was introduced in Malaysia as an alternative to controversial bayʻ al-ʻῑnah. However, the second type of tawarruq which is organized tawarruq was disputed by among scholars. The opponents claimed that the implementation of organized tawarruq is not complying Shariah requirements. The introduction of airtime credit as an underlying asset in tawarruq transaction by Sedania As Salam Capital Sdn Bhd (Sedania) is seems to neutralize the argumentation. Hence, this study aimed to review the implementation of tawarruq in personal financing product using airtime credit at Sedania’s first client which is RHB Islamic Bank (RHBIB). Interview sessions with the representatives of Sedania and RHBIB will be held in collecting the information of the modus operandi and also using the literature review in studying the tawarruq concept. The study found that choosing Sedania as a platform in doing tawarruq transaction by using airtime credit as the commodity is the best solution in personal financing product. However, the consumption of this underlying asset in bigger market such as corporate banking and treasury should be considered and more research about this are suggested.
Keywords: Tawarruq; Airtime Credit; RHB Islamic Bank; Sedania as Salam Capital Sdn Bhd; Personal Financing; Underlying Asset